2021
DOI: 10.1080/19420862.2021.1895540
|View full text |Cite
|
Sign up to set email alerts
|

Discovery-stage identification of drug-like antibodies using emerging experimental and computational methods

Abstract: There is intense and widespread interest in developing monoclonal antibodies as therapeutic agents to treat diverse human disorders. During early-stage antibody discovery, hundreds to thousands of lead candidates are identified, and those that lack optimal physical and chemical properties must be deselected as early as possible to avoid problems later in drug development. It is particularly challenging to characterize such properties for large numbers of candidates with the low antibody quantities, concentrati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
27
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(27 citation statements)
references
References 156 publications
(237 reference statements)
0
27
0
Order By: Relevance
“…Computational tools have been applied to identify drug-like antibodies that have favorable stability. 4 For viscosity prediction, Sharma et al found that viscosity is highly correlated with variable fragment (Fv) net charge and charge symmetry and weakly correlated with hydrophobicity. 5 Based on these three parameters, a linear equation was proposed to calculate viscosity at 180 mg/ml (pH 5.5 and 200 mM arginine-HCl).…”
Section: Introductionmentioning
confidence: 99%
“…Computational tools have been applied to identify drug-like antibodies that have favorable stability. 4 For viscosity prediction, Sharma et al found that viscosity is highly correlated with variable fragment (Fv) net charge and charge symmetry and weakly correlated with hydrophobicity. 5 Based on these three parameters, a linear equation was proposed to calculate viscosity at 180 mg/ml (pH 5.5 and 200 mM arginine-HCl).…”
Section: Introductionmentioning
confidence: 99%
“…Since self-association interactions are mechanistically more directly related to the solubility, viscosity and opalescence of the antibody formulation than to nonspecific antibody interactions that occur in vivo , it may be more difficult to identify any potential associations between AC-SINS and PBPK model-based parameters characterizing nonspecific interactions. 20 Further PBPK studies using additional antibodies would be needed to explore AC-SINS as a model-based predictor of antibody PK in humans.…”
Section: Discussionmentioning
confidence: 99%
“…Several experimental assays exist to assess antibody developability. 10 To measure polyspecificity, i.e., the propensity of an antibody to bind off-target molecules, binding to baculovirus particles, polyspecificity reagent, or cross-interaction chromatography have been explored. 11–13 In a recent study, polyspecificity was associated with poor clearance in human clinical trials, making it a critical parameter to consider in antibody lead selection.…”
Section: Introductionmentioning
confidence: 99%
“…Assays that are more demanding of protein quantity are also critical in assessing developability. 10 For example, antibodies delivered through subcutaneous injections require formulation and administration at high concentrations. 15 Highly viscous antibodies provide substantial challenges to subcutaneous delivery and manufacturing, making it necessary to identify antibodies with low viscosity to reduce the risk of clinical failure and increase patient compliance.…”
Section: Introductionmentioning
confidence: 99%